2021
DOI: 10.1186/s13099-021-00418-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus‐associated esophagitis on early esophageal cancer in immunocompetent host: a case report

Abstract: Background Cytomegalovirus (CMV)-associated gastrointestinal diseases usually occur in immunocompromised patients; however, few cases has also been described in healthy hosts despite still unclear pathological mechanisms. CMV esophagitis causes various lesions, such as erythematous mucosa, erosions, and ulcers, although such inflammatory changes can appear in superficial esophageal cancers or in surrounding areas. CMV-associated esophagitis has been also reported in cancer patients, but typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
3
1
Order By: Relevance
“…52 It was reported that HCMV reactivation was not only present in terminally advanced cancer patients, but with immune-competent ones as well making it necessary to suspect HCMV with pyrexia of unknown origin. 39,[53][54][55][56] HCMV reactivation could not be detected in any of the 93 cancer patients with mild to moderate level of immunosuppression after chemotherapy exposure, which is contrary to our results. 57 Schlick et al reported the case study of a patient with fever, pancreatic adenocarcinoma, and metastasis to the liver, lungs, and peritoneal cavity.…”
Section: Discussioncontrasting
confidence: 99%
“…52 It was reported that HCMV reactivation was not only present in terminally advanced cancer patients, but with immune-competent ones as well making it necessary to suspect HCMV with pyrexia of unknown origin. 39,[53][54][55][56] HCMV reactivation could not be detected in any of the 93 cancer patients with mild to moderate level of immunosuppression after chemotherapy exposure, which is contrary to our results. 57 Schlick et al reported the case study of a patient with fever, pancreatic adenocarcinoma, and metastasis to the liver, lungs, and peritoneal cavity.…”
Section: Discussioncontrasting
confidence: 99%
“…Our analysis also revealed an overrepresentation of pathways related to virus infections among the DEGs, which was not surprising given the well-established links between certain microbial species such as HPV [ 91 ], CMV [ 55 , 56 ] (Table 4 ), and ESCC. In addition, we also observed an overrepresentation of KEGG pathways related to protozoans such as Amoebiasis and Leishmaniasis in our analysis, which is an interesting finding because both of these infections are prevalent disease throughout tropical and subtropical regions of the world.…”
Section: Discussionsupporting
confidence: 66%
“…Literature evidences support these plausible microbial infections in ESCC. For example (i) Infection of several species of Leishmania was observed with Squamous Cell Carcinoma in Brazil and Iran [52][53][54], and a long term infection of it suspected to induce DNA methylation alterations triggering tumorigenesis [52], (ii) CMV infection associated gastrointestinal tract lesion-esophagitis in a Japanese patient observed with a moderately differentiated squamous cell carcinoma [55] and reactivation of CMV infection among esophageal cancer patients undergoing chemotherapy in Japan [56], (iii) Cervical cancer patients in India [57] and colon cancer patients in India and Japan [58,59] found with Amoebiasis. Further, Entamoeba histolytica infects epithelial cells expressing EhADH adhesin together with the EhCP112 cysteine protease and damage epithelium [60].…”
Section: Gene Ontology and Pathway Enrichment Of Degsmentioning
confidence: 99%
“… 18 However, as EC‐ESCC is not targeted in JCOG1217, the appropriate prophylactic treatment for EC‐ESCC remains unresolved. In addition, although this multi‐institutional questionnaire did not focus on the complications related to these treatments, many complications have been reported, 19 , 20 , 21 , 22 and it does not seem feasible to simply increase the dose and frequency of steroids in terms of efficacy and safety balance. Therefore, it is also important to identify the optimal prophylactic treatment after ESD for EC‐ESCC in a prospective multi‐institutional study.…”
Section: Discussionmentioning
confidence: 99%